Numerical solution of Navier stokes equation using control volume and finite element method - Adam Aigo, Musa (International Journal of Applied Mathematical Research, 2016)
The aim of this paper is twofold first we willÂ  provide a numerical solution of the Navier Stokes equation using the Projection technique and finite element method. The problem will be introduced in weak formulation and a Finite Element method will be developed, then solve in a fast way the sparse system derived. Second, the projection method with Control volume approach will be applied to get a fast solution, in iterations count.